PELAKSANAAN PERJANJIAN BAGI HASIL BANGUN RUMAH TOKO ANTARA PEMILIK TANAH DENGAN PENGELOLA DI KECAMATAN JAMBI TIMUR KOTA JAMBI - Nur Fauzia (Universitas Batanghari Jambi, 2014)
Among the products are very tempting for the present time in the field of trade in the city of Edinburgh is home store (shop), where it can be used as a store house of residence and / or place of business. Therefore people vying to build houses ditanahnya store.In terms of housing construction is not always done by the shop owner of the land, but entered into a collaboration with another person or party in the kind of wake-sharing agreement. In general wake-sharing agreements between land owners and shop managers, who want it is the owner of the land, but now has many agreements to shop wake desired results the first time by the management, in which managers are expecting the land from the owner of the land for the store.In the implementation of wake-sharing agreements between owners of land held by managers in the City of Edinburgh does not always run smoothly, let alone a very long period of agreement, then it is not likely arise various problems or obstacles in the implementation of the agreement.Keyword : agreements, profit sharing, land